Acute exposure guideline levels for selected airborne chemicals. Volume 11 - National Research Council (U.S.). Committee on Acute Exposure Guideline Levels; National Research Council (U.S.). Board on Environmental Studies and Toxicology; National Research Council (U.S.). Committee on Toxicology; National Research Council (U.S.). Division on Earth and Life Studies (Washington, D.C. : National Academies Press, 2012)
At the request of the Department of Defense and the Environmental Protection Agency, the National Research Council has reviewed the relevant scientific literature compiled by an expert panel and established Acute Exposure Guideline Levels (AEGLs) for several chemicals. AEGLs represent exposure levels below which adverse health effects are not likely to occur and are useful in responding to emergencies, such as accidental or intentional chemical releases in community, workplace, transportation, and military settings, and for the remediation of contaminated sites. Three AEGLs are approved for each chemical, representing exposure levels that result in: 1) notable but reversible discomfort; 2) long-lasting health effects; and 3) life-threatening health impacts. This volume in the series includes AEGLs for bis-chloromethyl ether, chloromethyl methyl ether, chlorosilanes, nitrogen oxides, and vinyl chloride.
Front Matter -- Preface -- Contents -- Introduction -- Appendixes -- 1 bis-Chloromethyl Ether: Acute Exposure Guideline Levels -- 2 Chloromethyl Methyl Ether: Acute Exposure Guideline Levels -- 3 Selected Chlorosilanes: Acute Exposure Guideline Levels -- 4 Nitrogen Oxides: Acute Exposure Guideline Levels -- 5 Vinyl Chloride: Acute Exposure Guideline Levels
Includes bibliographical references.
Online resource; title from PDF title page (National Academies Press, viewed on May 25, 2012).
eBooks on EBSCOhost
Keywords: Gases, Asphyxiating and poisonous; Hazardous Substances -- standards; Environmental Exposure -- standards; Hazardous Substances -- adverse effects; Gaz asphyxiants et délétères.; MEDICAL -- Toxicology; Gases, Asphyxiating and poisonous; Guideline